ASSOCIATE BETWEEN FAMILY SUPPORT WITH SELF-CARE BEHAVIOR OF PATIENTS WITH DIABETES MELLITUS TYPE 2. (Studies in work area of public health Jelakombo in Jombang Regency) - Ummi Fajarul Aini; Ahmad Rifai; Anin Wijayanti (JIWA INTER PLUS, 2011)
Diabetes mellitus (DM) type 2 in the majority of countries have developed as a result of social and cultural fast change, the ever increasing aging population, increasing urbanization, dietary changes, reduced physical activity and unhealthy behavior patterns Type 2 diabetes mellitus is a chronic disease who need long-term care and require management self-care (self-care) and support from the family to prevent acute and chronic complications. This study aimed to determine the relationship of family support with self-care behavior of patients with diabetes mellitus type 2. This study was an analytical cross sectional correlation with a population of 236 respondents and sampling the probability sampling technique with random sampling approach with a sample size of 99 people. Independent variables are the independent variables of family support and self-care behaviors that people with type 2 diabetes mellitus measuring tool used in this study was a questionnaire. The data is processed through the editing stage, coding, processing, and cleaning. Then tested with Pearson correlation. Based on the results of Pearson correlation test using SPSS on the error rate ρ ≤ 0.05. Based on the results obtained ρ = 0.012 and r = 0.252 then H1 is accepted. The result can be concluded that there was a relationship between singnifican family support with self-care behaviors of patients with diabetes mellitus type 2.